Sustaning Women Economic Empowerment: A Gender Perspective Source Of Electricity Generation - Adesuwa Omage; O.K. Asikhia; E.E, Oriarewo; S.O Omoruyi; D.J. Idiata; L.O. Obanor (Universitas Ahmad Dahlan, 2022)
Women require vocational skills for economic stability and alternative income. Despite attempts to empower women in low and middle-income nations, they still face obstacles, notably with energy supply, a critical component for their productivity and the subject of this study. Five (5) research questions were raised. The study adopted the descriptive survey research design. The entire population of 309 female artisans in Edo South, Central and North Senatorial Districts was used as sample. The questionnaire was analysed using Mean and Standard Deviation. The decision rule was based on 3.0 such that any calculated mean equal or greater than 3.0 was regarded as agreed while less than 3.0 as disagreed. The study found that women had challenges with the conventional alternative source of power generating set and recommended among others that experts should consider a gender perspective in design and construction in order to alleviate the sufferings of female artisans. Women require vocational skills for economic stability and alternative income. Despite attempts to empower women in low and middle-income nations, they still face obstacles, notably with energy supply, a critical component for their productivity and the subject of this study. Five (5) research questions were raised. The study adopted the descriptive survey research design. The entire population of 309 female artisans in Edo South, Central and North Senatorial Districts was used as sample. The questionnaire was analysed using Mean and Standard Deviation. The decision rule was based on 3.0 such that any calculated mean equal or greater than 3.0 was regarded as agreed while less than 3.0 as disagreed. The study found that women had challenges with the conventional alternative source of power generating set and recommended among others that experts should consider a gender perspective in design and construction in order to alleviate the sufferings of female artisans.